195k views
2 votes
3Q + 4T = 26. P=2T=3Q l. What is 6P?

The answer is 52 but I don’t understand how they got this answer

2 Answers

3 votes

Answer:

see explanation

Explanation:

Given P = 2T = 3Q, then

3Q + 4T = 26 can be expressed as

P + 2P = 26

3P = 26 ( multiply both sides by 2 )

6P = 52 ← as required

User Alou
by
5.6k points
3 votes

Step-by-step explanation and answer:

The given equations P=2T=3Q can be split up into

P=2T..................(1)

P=3Q................(2)

since they are all equal.

Rewrite the given equation

3Q + 4T = 26 .............(3)

as

3Q + 2(2T) = 26 ...........(4)

and substitute (1) and (2) into (4)

P + 2(P) = 26 .................(5)

Multiply (5) by two to get

6P = 2*26 = 52 ..............(6)

as given.

User SnapShot
by
5.5k points